2000
DOI: 10.1152/ajpregu.2000.278.6.r1685
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an intrarenal renin-angiotensin system in the rainbow trout,Oncorhynchus mykiss

Abstract: Physiological and molecular approaches were used to investigate the existence of an intrarenal renin-angiotensin system (RAS) in rainbow trout. Inhibition of angiotensin-converting enzyme by captopril (5 x 10(-4 )M) rapidly decreased vascular resistance of the trunk of the trout, perfused at 19 mmHg, resulting in an increased perfusate flow rate and a decreased intrarenal dorsal aortic pressure. A profound diuresis occurred in the in situ perfused kidney and reflected both increased glomerular filtration rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The perfused trunk preparation has been used in freshwater-acclimated rainbow trout Oncorhynchus mykiss for the investigation of renal actions of AVT (3,8) and ANG II (8,11). The present study is the first time that use of a perfused trunk preparation has been reported in an elasmobranch fish.…”
Section: Discussionmentioning
confidence: 83%
“…The perfused trunk preparation has been used in freshwater-acclimated rainbow trout Oncorhynchus mykiss for the investigation of renal actions of AVT (3,8) and ANG II (8,11). The present study is the first time that use of a perfused trunk preparation has been reported in an elasmobranch fish.…”
Section: Discussionmentioning
confidence: 83%
“…The TmG found in this study is similar to findings in another in vivo study (Gray and Brown, 1985;Table·2). However, it is approximately double compared with findings on in situ perfused trout kidney studies (Amer and Brown, 1995;Brown et al, 2000;Table·2). Part of these differences could be accounted for by variations in experimental temperatures, as TmG varies with temperature, with higher temperatures yielding higher TmGs (MacKay and Beatty, 1967).…”
Section: Discussionmentioning
confidence: 87%
“…Pressure effects would be very rapidly achieved and a restoration of blood pressure would be likely to inhibit further angiotensin formation. A further part of the recovery, at least in FWacclimated lampreys, could involve a reduction in urine flow rates initiated by angiotensin, as has been shown to occur in teleosts (Brown and Balment, 1997;Brown et al, 2000). Studies are required to describe fully the renal actions of the lamprey RAS, but Asn 1 ,Val 5 -Ang II at 10 -10 or 10 -9 ·mol·min -1 ·kg -1 ·body·mass has been shown to reduce urine flow rates of FW-acclimated Lampetra fluviatilis and Petromyzon marinus (J.…”
Section: Discussionmentioning
confidence: 93%